Analysis on Mobility Management of Multiple PLMNs EUTRAN Networking - Shangkun Xiong; Wenyi Li; ZhaoYe ,; Jie Chen; Qingyang Wang (Dianxin kexue)
The use cases of two or multiple PLMNs for one operator were provided.And then,the procedures of mobility management of multiple-PLMN networking were analyzed for different use cases.As a conclusion,it was feasible for a operator to achieve normal mobility management and keep continuity of service when EUTRAN networking with multiple PLMNs.